COMPARISON OF PROBLEM BASED LEARNING WITH PROJECT BASED LEARNING ASSISTED BY MOBILE BASED LEARNING MEDIA ON STUDENTS’ LEARNING OUTCOMES - Nugroho, Andhik Catur; Irianto, Wahyu Sakti Gunawan; Herwanto, Heru Wahyu (Letters in Information Technology Education (LITE), 2018)
This Study presents the utilization of mobile-based learning media in a computer and basic networks. The use of mobile-based interactive media aims to help vocational students majoring in Computer and Network Engineering in learning productive subjects in computers and basic networks. Therefore, this study has a three purposes there are: (1) to discover the influence of Problem Based Learning (PBL) model on students? learning outcomes, (2) to discover the influence of Project Based Learning (PjBL) model on students? learning outcomes, and (3) to compare the PBL and PjBL on students? learning outcomes. The quasi experiment method is used in this research including control and experiment group with different treatment. The subject consists of 108 10th grade students of SMKN 1 Bagor. Data analysis using quantitative technique in this study. Result shows that there is good impact from PBL and PjBL model implementation assisted with mobile-based learning media on the students? learning outcome. In addition, there is a difference between PBL and PjBL implementation that the PBL give a more significant effect on students? learning outcomes.